2019
DOI: 10.2147/cmar.s218427
|View full text |Cite
|
Sign up to set email alerts
|

<p>Increased expression of heat shock protein (HSP) 10 and HSP70 correlates with poor prognosis of nasopharyngeal carcinoma</p>

Abstract: BackgroundHeat shock proteins (HSPs) are a large family of chaperones implicating in occurrence and progression of tumor. In our previous study, we found HSP10 correlates with poor prognosis of oral squamous cell carcinoma and astrocytoma. HSP70 is also an important part of this family and whether the alterations of HSP10 and HSP70 expression and their common expression correlates with carcinogenesis and progression of nasopharyngeal carcinoma (NPC) has not been reported.MethodIn this study, we investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In addition, HSP10 plays a crucial role in cancer progression and development [ 26 ], as indicated by its increased expression in many kinds of malignant tumors, including astrocytoma, colorectal cancer, and liver cancer [ 7 , 27 , 28 ]. It has suggested that HSP10 might be an independent prognostic factor for poor prognosis of nasopharyngeal carcinoma and invasive ductal breast carcinoma [ 29 , 30 ]. In this study, we found higher HSP10, HSP60 and Mcl-1 expression in NSCLC compared with Non-CLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HSP10 plays a crucial role in cancer progression and development [ 26 ], as indicated by its increased expression in many kinds of malignant tumors, including astrocytoma, colorectal cancer, and liver cancer [ 7 , 27 , 28 ]. It has suggested that HSP10 might be an independent prognostic factor for poor prognosis of nasopharyngeal carcinoma and invasive ductal breast carcinoma [ 29 , 30 ]. In this study, we found higher HSP10, HSP60 and Mcl-1 expression in NSCLC compared with Non-CLT.…”
Section: Discussionmentioning
confidence: 99%
“…(F) Lung ADC patients with low Mcl-1 expression survived longer than those with high one (P = 0.026, two sided). prognostic factor for poor prognosis of nasopharyngeal carcinoma and invasive ductal breast carcinoma [29,30].…”
Section: Furthermore We Analyzed the Correlation Between Survival Ramentioning
confidence: 99%
“…The immunohistochemistry (IHC) and immunocytochemistry (ICC) are reliable and widely used techniques for the assessment of HSP levels. They have been successfully applied for evaluation of expression levels of HSP to investigate their role in the pathogenesis of cutaneous Lichen planus 47 , psoriasis 48 or to study the potential of HSP as a biomarker of inflammatory bowel disease 49 or even as a cancer biomarker 43 , 50 , 51 . Human dermal fibroblasts adhered to the Petri dish bottom were exposed to a series of THz pulses with average power ( and ) for 180 min (group 1).…”
Section: Resultsmentioning
confidence: 99%
“…The product was calculated using the formula: labeling score × intensity scores. Low and high WNT8B expression score was defined according to Log-rank statistical analysis with respect to the significance of NPC patient survival [ 28 , 29 , 30 ]. A final score of 1–2 indicated low expression and 3–12 indicated high expression.…”
Section: Methodsmentioning
confidence: 99%